Petroleum waste treatment and pollution control - Jafarinejad, Shahryar (Butterworth-Heinemann, imprint of Elsevier, 2017)
Petroleum Waste Treatment and Pollution Control combines state-of-the-art and traditional treatment and control methods for removing, controlling, and treating problems, such as groundwater contamination, aromatics, oil, grease, organic removal, and VOCs. The book is divided into seven chapters, with the first briefly introducing readers to the petroleum industry. The second and third chapters explain wastes in the petroleum industry and focus on its environmental impact, its regulations, and protection options. Chapters four, five, and six discuss the treatment of air emissions, oily wastewater, solid wastes, and disposal methods. The final chapter provides remediation processes.